IVAN FRANKO’S EARLY DRAMATURGY: GENESIS, PECULIARITIES OF DEVELOPMENT - Khorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article researches genesis and peculiarities of the development of Ivan Franko’s early dramaturgy are researched. On the background of social-national and cultural-artistic life in Halychyna of that time it proves the organic unity of creative searches of Franko-playwright, the employment of traditional and innovative techniques of drama description in his plays, determines his place in the literary-theatrical process of Western Ukraine.